Self-Healing, Solvent-Free, Anti-Corrosion Coating Based on Skin-like Polyurethane/Carbon Nanotubes Composites with Real-Time Damage Monitoring - Hui Kong; Xiaomin Luo; Peng Zhang; Jianyan Feng; Pengni Li; Wenjie Hu; Xuechuan Wang; Xinhua Liu (Nanomaterials, 2022)
Self-healing anti-corrosion materials are widely regarded as a promising long-term corrosion protection strategy, and this is even more significant if the damage can be monitored in real-time and consequently repaired. Inspired by the hierarchical structure of human skin, self-healing, solvent-free polyurethane/carbon nanotubes composites (SFPUHE-HTF-CNTs) with a skin-like bilayer structure were constructed. The SFPUHE-HTF-CNTs were composed of two layers, namely, a hydrophobic solvent-free polyurethane (SFPUHE-HTF) containing disulfide bonds and fluorinated polysiloxane chain segments consisting of a self-healing layer and CNTs with good electrical conductivity consisting of a corrosion protection layer, which also allowed for the real-time monitoring of damage. The results of corrosion protection experiments indicated that the SFPUHE-HTF-CNTs had a low corrosion current density (8.94 × 10−9 A·cm−2), a positive corrosion potential (−0.38 V), and a high impedance modulus (|Z| = 4.79 × 105 Ω·cm2). The impedance modulus could still reach 4.54 × 104 Ω·cm2 after self-healing, showing excellent self-healing properties for anti-corrosion protection. Synchronously, the SFPUHE-HTF-CNTs exhibited a satisfactory damage sensing performance, enabling the real-time monitoring of fractures at different sizes. This work realized the effective combination of self-healing with corrosion protection and damage detection functions through a bionic design, and revealed the green, and low-cost preparation of advanced composites, which have the advantage of scale production.